Changes in fat contents of US snack foods in response to mandatory trans fat labelling - Van Camp, Debra; Hooker, Neal H; Lin, Chung-Tung Jordan (Public health nutrition, 2012)
Impact of mandatory trans fat labelling on US snack food introductions is examined. Using label information, lipid ingredients and fat profiles are compared pre- and post-labelling. Key products in the US snack food industry contribute significant amounts of artificial trans fat. Industry efforts to reformulate products to lower trans fat may alter the overall fat profile, in particular saturates. Composition data for more than 5000 chip and cookie products introduced for sale between 2001 (pre-labelling) and 2009 (post-labelling) were analysed. One-way ANOVA was used to test for significant changes in saturated fat content per serving and the ratio of saturated to total fat. The shares of chip and cookie introductions containing partially hydrogenated vegetable oil declined by 45 and 42 percentage points, respectively. In cookies, there was an increase of 0·49 (98 % CI 0·01, 0·98) g in the average saturated fat content per 30 g serving and an increase of 9 (98 % CI 3, 15) % in the average ratio of saturated to total fat. No statistically significant changes in fat content were observed in chips. This research suggests that, holding other factors constant, the policy has resulted in a decreased use of partially hydrogenated vegetable oil in chip products without a corresponding increase in saturated fat content, but led to significantly higher levels of saturated fat and ratio of saturated fat to total fat in cookie products.